Pengaruh Profitabilitas, Likuiditas, dan Leverage terhadap Tarif Pajak Efektif pada Perusahaan Sub Sektor Makanan dan Minuman yang terdaftar di BEI - Sri Suhartini; Emi Masyitah (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The effective tax rate is the amount of the tax burden calculated from the tax base multiplied by the applicable tax rate. This research aims to test and analyze the influence of profitability, liquidity and leverage on effective tax rates in food and beverage sub-sector companies listed on the Indonesian Stock Exchange. The research method used is quantitative research, with an associative approach. The data source used is secondary data. The population used in the research was 26 companies and the sample in this research was 10 companies. The sampling technique used was purposive sampling technique. Data collection techniques are documentation methods and library study methods. Data analysis techniques in this research use Descriptive Statistical Analysis, Classic Assumption Test, Multiple Linear Regression Analysis, Hypothesis Testing, and Coefficient of Determination (R2). The results of this research show that profitability has an effect on the effective tax rate, liquidity has no effect on the effective tax rate, and leverage has an effect on the effective tax rate. The results of the analysis prove that profitability, liquidity and leverage influence the effective tax rate.